2018
DOI: 10.1002/ppul.24218
|View full text |Cite
|
Sign up to set email alerts
|

Serum neurotrophins at birth correlate with respiratory and neurodevelopmental outcomes of premature infants

Abstract: Objective Preterm birth is a significant cause of infant morbidity and mortality, which are primarily the result of respiratory and neurodevelopmental complications. However, no objective biomarker is currently available to predict at birth the risk and severity of such complications. Thus, we sought to determine whether serum neurotrophins concentrations measured at birth correlate with risk for later development of bronchopulmonary dysplasia (BPD) and long‐term neurodevelopmental outcomes. Methods This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…However, we did not rule out the possibility that preterm newborns might also have altered expression and production of these NFs, since our meta-analyses were performed with a small number of studies, which highlights the under exploration of some NFs. Interestingly, in some of the reviewed studies, we found relevant clinical correlations between NGF levels and neurodevelopmental outcomes ( 25 , 29 ). Suggesting that these NFs should be further explored.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, we did not rule out the possibility that preterm newborns might also have altered expression and production of these NFs, since our meta-analyses were performed with a small number of studies, which highlights the under exploration of some NFs. Interestingly, in some of the reviewed studies, we found relevant clinical correlations between NGF levels and neurodevelopmental outcomes ( 25 , 29 ). Suggesting that these NFs should be further explored.…”
Section: Discussionmentioning
confidence: 89%
“…In addition to preterm and term comparisons performed in the meta-analyses, findings showing an association between NFs and clinical outcomes were reported in some studies ( Table 1 ). Simpson et al ( 29 ) found that lower levels of serum BDNF were significantly associated with a higher risk of bronchopulmonary dysplasia among preterm newborns. Furthermore, Dhobale et al ( 21 ) showed a positive correlation between BDNF levels and gestational weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is the first to our knowledge examining the relationship between cord serum BDNF levels at birth with BSID-III scores at 12–14 months. One previous study assessed the relationship between BSID-III scores and cord serum BDNF at 24 months and reported no association between serum BDNF levels at birth and BSID-III cognitive, language or motor scores ( Simpson et al, 2019 ). Perera et al (2015) identified a positive association between plasma BDNF from cord blood and BSID-III mental development index scores at 2 years; however this relationship disappeared by 3 years of age ( Perera et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the seemingly never‐ending search for preventive treatments, Cuna et al 16 compared ventilated prematurely born patients who received dexamethasone between day 14 and day 28 with those who received treatment after 28 days and found that the earlier‐treated group had better outcomes. To better identify those prone to develop BPD, molecular markers of susceptibility, such as brain‐derived neurotrophic factor 17 are being studied since we know that genetic contribution to BPD is significant 15 . Using inbred congenic neonatal mice, Tiono et al 18 showed significant genetic strain‐dependent susceptibility to hyperoxia and strain‐dependent variation in antioxidant responses.…”
mentioning
confidence: 99%